IN THE POETICAL WORLD OF LOVE (LYRICS BY MARIA VAYNO) - Khorob М. B. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2022)
Maria Vayno is a well-known master of the modern short story ("Sketches on the Doors" (2011), "Stanislavski Frescoes" (2012), novels in short stories ("The Warm Yard, or Rhapsody of the String Quartet" (2001), "Passionaria" (2012), "Notes her life, or love in the proposed circumstances" (2020), "The Editor" (2022), film scripts ("The Man on Credit, or the Fourth Option" (2000, etc.), the manual "Screenplay Mastery" (2015), a total of twenty editions). Actually, for the best of them, the writer was awarded the title of laureate of the city and regional awards in the field of literature named after Ivan Franko and Vasyl Stefanyk, All-Ukrainian – named after Hryhor Tyutyunnyk, twice laureate of the All-Ukrainian "Coronation of Words" competition in the "screenplay" and "prose" nominations. But she started her work with lyrics. The purpose of the article: since today there is no synthesized understanding of the author’s poems (with the exception of individual reviews of the first or second collection (for example, E. Baran, R. Mykhailovskyi and the mostly informative plan of reporting on presentations in local periodicals) to analyze Maria Vaino’s poetic books "Terpity" (1992), "Ariadna’s Thread" (1999) and "Uzhhorod Cycle" (2018), tracing the dynamics of the feelings of the lyrical heroine from the beginning of the author’s work, which falls on the last decade of the 20 th century, to the end of the second decade of the 21 st century. Research methods: concrete-historical, hermeneutic, as well as receptive aesthetics. Scientific novelty: for the first time in literary science, the inner world of the lyrical heroine, the movement of her feelings, the motive and figurative sphere of the lyric have been meaningfully synthesized. The practical significance of the article – its results can be used during the study of Maria Vaino’s work in general as the beginning of a literary path and a typological comparison with the work of other writers of lyrics or with the author’s prose work.